1997
DOI: 10.1001/archpsyc.1997.01830200083012
|View full text |Cite
|
Sign up to set email alerts
|

Noradrenergic and Serotonergic Function in Posttraumatic Stress Disorder

Abstract: These data suggest the presence of 2 neurobiological subgroups of patients with PTSD, one with a sensitized noradrenergic system, and the other with a sensitized serotonergic system.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
122
1

Year Published

1998
1998
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 284 publications
(128 citation statements)
references
References 79 publications
5
122
1
Order By: Relevance
“…However, the lack of correlation between these changes suggests that individual differences may influence which neurobiological system is affected in each specific case, and that different subjects within the same diagnostic category may have different response profiles. A recent pharmacological challenge study also suggested the presence of neurobiologically distinct subgroups of PTSD patients (Southwick et al 1997). This is consistent with our suggestion that PTSD patients are not a neurobiologically homogenous group.…”
Section: Resultssupporting
confidence: 92%
“…However, the lack of correlation between these changes suggests that individual differences may influence which neurobiological system is affected in each specific case, and that different subjects within the same diagnostic category may have different response profiles. A recent pharmacological challenge study also suggested the presence of neurobiologically distinct subgroups of PTSD patients (Southwick et al 1997). This is consistent with our suggestion that PTSD patients are not a neurobiologically homogenous group.…”
Section: Resultssupporting
confidence: 92%
“…PTSD patients exhibit a resistance to extinction (Orr et al, 2000) and NE hyperresponsiveness to traumatic stimuli (Geracioti et al, 2006), suggesting that NE hyperresponsiveness may be responsible for impairing extinction learning. Yohimbine, which causes NE hyperresponsiveness, can induce panic attacks in PTSD patients (Southwick et al, 1997(Southwick et al, , 1999). In contrast, we found that extinction is dependent on activation of noradrenergic ␤-receptors in IL.…”
Section: Discussionmentioning
confidence: 99%
“…Norepinephrine (NE) not only plays an important role in mood and arousal, but also in the encoding, retrieval, and reconsolidation of emotional memories (9)(10)(11)(12)(13). Endogenous NE signaling is elevated in PTSD and drugs that block NE receptors are already being used with some success to either prevent or treat PTSD, including its symptoms of hyperarousal and nightmares (14)(15)(16)(17)(18). Clinically effective noradrenergic drugs include the α1-adrenoceptor antagonist, prazosin, and the β1/β2-adrenoceptor antagonist, propranolol (17,(19)(20)(21).…”
mentioning
confidence: 99%